Ethics from the Bench Podcast - Balachandran, Rekha; Akinsiku, Adegboyega (Online Ethics Center, 2021)
In this podcast, participants discuss how views on RCR and ethics are shaped by one's experiences and upbringing, as well as whether research integrity should be integrated into the research curriculum from the start.
Multimedia
Original submission date: 2023-08-17T19:13:02Z
Keywords: Engineering; Research Ethics; Social Justice; Equity; Inclusion; Teaching Ethics in STEM; Goals of Ethics Education; Teaching Ethics